Family Ownership, Family Control, and The Level of Com-pany Debt (Study on Family Business Listed on the Indone-sia Stock Exchange) - Putri Ayu Gustia Ningrum; Abel Tasman (Pusat Riset dan Inovasi Nasional, 2025)
Family firms have a significant contribution to the Indonesian economy, but their financial decisions, especially regarding the use of debt, often show results that are inconsistent with existing theories. This study aims to analyze the effect of family ownership and family control on the debt level of family firms listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. This study employs a quantitative approach, utilizing a panel data regression method. The sample consists of 81 family firms selected based on certain criteria, and data obtained from annual reports published on the IDX. The dependent variable is the level of company debt, as measured by the Debt-to-Equity Ratio (DER), while the independent variables are family ownership and family control. The control variables used are company size and company age. The results show that family ownership has a positive and significant effect on DER, while family control has a negative and significant effect on DER, indicating that companies with strong family ownership and control tend to avoid the use of high debt. These findings support agency theory, which states that family involvement in the ownership and supervision of the company can reduce agency conflicts and financial risks. This study puts pressure on family firms to pay attention to ownership structure and governance in making financing decisions.